Talent Management Practices in the South African Public Service - Prince Chukwuneme Enwereji; Uwizeyimana Dominique Emmanuel (UIN Sunan Gunung Djati, 2022)
Talent management refers to the attraction, selection, and retention of employees, which involves a combination of HR processes across the employee life cycle. This study explored the best practice in talent management to ensure high potential talents are employed and retained due to the rising rate of employee turnover in the South African public service. A literature review and meta-analysis were conducted to explore different authors' views on the three main objectives of the study, which are to know the competencies of talent managers in developing high potential employees; explore the mechanisms talent managers can adopt in keeping high potential employees and to reveal the best practices in talent management. Findings from the study revealed that talent management is essential in assisting the employees in advancing their skills, improving their performance, and feeling engaged and motivated, thus allowing them to achieve desired goals. The ability to facilitate good planning, decision-making, change management, interpersonal relationships, emotional intelligence, programme implementation, and learning opportunities are the competencies required of talent managers to develop potential talents. Effective communication and feedback, promotion and advancement, efficient leadership, work-life balance, good organisational culture, development and training, and organisational commitment are the competencies required of talent managers to retain talents in the organisation. Regarding the best talent management practice, the study recommended that talent managers should specify the skills they need and select from a diverse pool of candidates. Other factors include onboarding practices, learning and development, performance management, an effective reward system, and a succession plan.